Existe facilitação vegetal em campo rupestre sobre canga no Parque Estadual da Serra do Rola Moça, MG? - Fernanda Cristina Guilherme (2011)
The aim of this study was to evaluate the facilitation potential of Acianthera teres Lychnophora pinaster, Microlicia martiana, Mimosa calodendron, Stachytarpheta glabra, Vellozia compacta, and Vellozia graminea in an area of ironstone outcrop in Rola Moça State Park. Data on temperature, moisture and light were collected during the rainy and dry seasons from each species (15 individuals for temperature and moisture and 30 for light) and in an open area, without influence of species, as control. Organic matter was collected in both seasons to compare the amount accumulated under the individuals. To determine the richness and abundance of plants, 20 individuals of each species above were selected. Every plant found below or near each individual was recorded and identified. These data collected in the rainy and dry seasons were compared with those in open areas, adjacent to the species and with similar area. Data on temperature and moisture were collected at 8, 12 and 16 hours. In the rainy season the species showed temperature and moisture milder than the values of open area than in dry season. M. calodendron, S. glabra and V. Compacta remained milder temperatures and moisture in the rainy season and in the dry season only the first stood easing these variables. V. graminea and A. teres were the species with higher temperatures and lower moisture, similar to the values of open area. The light intensity bellow the canopy of species (except A. teres and V. graminea that were not evaluated for this variable) showed values lower than in open areas at both seasons, S. glabra and V. compacta showed the highest values. A. teres showed the highest amount of litter and S. glabra the least. Regarding richness and abundance, these were highest in the rainy season. No differences were found in species richness or abundance between individuals and their corresponding open area in the rainy season. However, in the dry season, the abundance was significantly higher in the open area next to the individuals of L. pinaster, M. martiana and V. compacta, being the same for richness for the latter specie. The results show an improvement of the microclimate next to some species relative to the open area, which could lead to facilitation. However, data on richness and abundance do not confirm that any of the focal species is a good nurse plant despite the improvements guaranteed by some. The topography heterogeneity ensuring the presence of nurse objects or the canga abiotic stress may be possible causes for not having found nurse effects in this work.